(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
Currently, the main part of the protein requirement of the human body is accounted for by peas and lentils, which are leguminous crops. In recent years, there have been many cases of seeds rotting without sprouting and plants dying due to severe damage caused by various diseases as a result of the planting of imported pea and lentil seeds by farms. It also leads to excessive costs as the cultivated pea and lentil stalks are not adapted to harvest by the machinery. In the study, 20 winter chickpea genotypes were evaluated and selected under irrigated field conditions. Winter chickpea genotypes were determined by parameters such as growth period.